Assyrian Rulers of the Third and Second Millenia BC (To 1115 BC) - Grayson, Albert Kirk (Book collections on Project MUSE., 1987)
A collection of the texts of inscriptions the originals of which are now scattered in museums throughout the world. Provides commentary, bibliography, transliteration from the cuneiform, and English translation from the Sumerian or Abkadian. Each text is complete, and is collated against the original whenever possible. Where a text has been conflated from several inscriptions, a full transliteration is included among the four microfiche cards in a pocket inside the back cover. The first of a projected series covering Mesopotamia. For dedicated students, of the early Middle East. A. Kirk Grayson.